1993
DOI: 10.1163/156853893x00048
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory experiment on interspecific competition between tadpoles of Geocrinia victoriana and Pseudophryne semimarmorata (Anura, Myobatrachinae)

Abstract: Larval growth of Geocrinia victoriana and Pseudophryne semimarmorata was studied in tanks housing tadpoles of either species and mixed groups, providing the same density (individuals/water volume) in all containers. Tadpoles of P. semimarmorata were larger at hatching than G. victoriana, they reached metamorphic climax earlier and at larger sizes. In mixed groups, P. semimarmorata experienced relaxation of intraspecific competition; they metamorphosed at bigger sizes than controls kept only with conspecifics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Asymmetric competition is not uncommon among tadpoles. Indeed, several experimental studies have shown tadpoles of one species to have a big impact on tadpoles of a second species, while tadpoles of the second species have little impact on the first species (Smith‐Gill and Gill 1978, Wilbur 1982, 1987, Morin and Johnson 1988, Griffiths 1991, Werner 1992, Gollmann and Gollmann 1993, Warner et al 1993, Kupferberg 1997, Bardsley and Beebee 1998, 2000, 2001, Parris and Semlitsch 1998, Werner and Glennemeier 1999, Relyea 2000, Goméz‐Mestre and Tejedo 2002). We found that gray treefrog tadpoles ( Hyla versicolor ) were more affected by intraspecific competition than interspecific competition, while green frog tadpoles ( Rana clamitans ) were more affected by interspecific competition than intraspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric competition is not uncommon among tadpoles. Indeed, several experimental studies have shown tadpoles of one species to have a big impact on tadpoles of a second species, while tadpoles of the second species have little impact on the first species (Smith‐Gill and Gill 1978, Wilbur 1982, 1987, Morin and Johnson 1988, Griffiths 1991, Werner 1992, Gollmann and Gollmann 1993, Warner et al 1993, Kupferberg 1997, Bardsley and Beebee 1998, 2000, 2001, Parris and Semlitsch 1998, Werner and Glennemeier 1999, Relyea 2000, Goméz‐Mestre and Tejedo 2002). We found that gray treefrog tadpoles ( Hyla versicolor ) were more affected by intraspecific competition than interspecific competition, while green frog tadpoles ( Rana clamitans ) were more affected by interspecific competition than intraspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…These hormonal influences can occur at the level of independently programmed and regulated tissue‐specific (“peripheral”) responses to TH and/or at the level of the hypothalamus–pituitary–thyroid gland axis, which controls tissue transformation “centrally” (Denver 1996; Shi et al 1996). Whereas several studies have shown two species may differ in larval period duration when reared under laboratory conditions (Rafinska 1991; Gollmann and Gollmann 1993; Ptacek 1996), no previous study has examined potential endocrine basis for this difference or put such endocrine comparisons in a phylogenetic context. Here, we tested the hypothesis that differences in TH physiology, specifically tissue TH content and in vitro tissue sensitivity and responsivity to TH, correlate with differences in larval period duration between spadefoot toad species.…”
Section: Introductionmentioning
confidence: 99%
“…Various descriptions of the embryonic and larval development of the two eastern exotrophic species have been published (Littlejohn and Martin 1964;Martin 1967;Littlejohn et al 1971;Watson and Martin 1973;Martin and Littlejohn 1982;Gollmann and Gollmann 1991a,b, 1992a,b, 1993, 1996aAnstis 2002). For the southwestern species, there are studies including some developmental descriptions of G. leai and G. rosea by Main (1957Main ( , 1965 and of G. vitellina by Mitchell (2001).…”
Section: Introductionmentioning
confidence: 99%